(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
A list of all adventitious species found in the reserve’s floodplain is presented with their ecocenotic characteristics. Analysis of geographic origin, immigration time, degree of naturalization and expansion, roles in consortia and coenoses, coenology and features of generative process is carried out for adventitious flora. The group of the most expansive adventive species is detected.